LO036: The influence of cognitive rest and graduated return to usual activities emergency department discharge instructions on symptoms of minor traumatic brain injury. (2nd June 2016) - Varner, C.; McLeod, S.L.; Nahiddi, N.; Lougheed, R.; Borgundvaag, B.
Abstract : Introduction: It is estimated 15-50% of patients with a mild traumatic brain injury (MTBI) diagnosed in the emergency department (ED) will develop post-concussive syndrome (PCS). Although expert consensus recommends cognitive rest and graduated return to usual activities, these interventions are not based on prospective clinical evidence. The objective of this study was to determine if patients randomized to graduated return to usual activity discharge instructions had a decrease in their Post-Concussion Symptom Score (PCSS) 2 weeks after MTBI compared to patients who received usual care MTBI discharge instructions.Methods: This was a pragmatic, randomized trial of adult (18-64 years) patients presenting to an academic ED (annual census 65, 000) with chief complaint 'head injury' occurring within 24 hours of ED visit. Patients were contacted by text message or phone 2 weeks post ED discharge and again at 4 weeks and asked to complete a validated, 22 item questionnaire to determine if there was a change in their PCSS. Secondary outcomes included change in PCSS at 4 weeks, number follow-up physician visits, and time off work/school.Results: 118 patients were enrolled in the study (58 in the control group and 60 in the intervention). Mean (SD) age was 35.2 (13.7) years and 43 (36.4%) were male. There was no difference with respect to change in PCSS at 2 weeks (10.5 vs 12.8; Δ 2.3, 95% CI: 7.0, 11.7) and 4 weeks post-ED discharge (21.1 vs 18.3; Δ 2.8, 95% CI: 6.9, 12.7) for the intervention and control groups, respectively. The number follow-up physician visits and time off work/school was similar when the groups were compared.Conclusion: Results from this study suggest graduated return to usual activity discharge instructions do not impact rate of resolution of MTBI symptoms 2 weeks after ED discharge. Given patients continue to experience low to moderate symptoms 2 weeks after MTBI, more investigation is needed to determine how best to counsel and treat patients with post-concussive symptoms.